Brief Report: Selection of HIV-1 Variants With Higher Transmission Potential by 1% Tenofovir Gel Microbicide - Ngandu, Nobubelo K.; Carlson, Jonathan M.; Chopera, Denis R.; Ndabamb, Nonkululeko; Karim, Quarraisha Abdool; Karim, Salim Abdool; Williamson, Carolyn (Journal of Acquired Immune Deficiency Syndromes, 2017)
Background: Women in the CAPRISA 004 trial assigned to use 1% tenofovir (TFV) microbicide gel, who became HIV-1 infected, had higher viral load set-point and slower antibody avidity maturation compared with placebo participants. We investigated whether TFV gel was selected for viruses with altered genetic characteristics. Setting: The participants of the CAPRISA 004 trial (n = 28 TFV and 43 placebo) were from KwaZulu-Natal Province, South Africa and were infected with HIV-1 subtype C. After HIV-1 diagnosis, they were recruited into the CAPRISA 002 cohort. Methods: We analyzed gag sequences from the earliest time point post infection (within 3 months of estimated time of infection). Transmission index was measured using a model which predicts the likelihood of an amino acid to be transmitted. Phylogenetic distance from a regional consensus sequence was calculated from a maximum likelihood phylogenetic tree. Results: Transmission index and distance from the most common (consensus) sequence have been shown to be markers of transmission fitness. We found that viruses infecting TFV gel recipients were closer to the consensus sequence of regional strains (P = 0.003) and had higher transmission index (P = 0.01). The transmission index was weakly correlated with concomitant viral load (Spearman r = 0.22, P = 0.06). Conclusion: Decreased acquisition risk may have increased the barrier to infection therefore selecting for fitter, more consensus-like viruses. Such virus fitness effects will need to be considered for future pre-exposure prophylaxis and vaccine trials.